1990
DOI: 10.1159/000177592
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in Growing Male Rats: A Cause of Development of Cardiomyopathy

Abstract: Weanling male rats were fed a purified iron-adequate, a purified iron-deficient or a commercial diet for 12 weeks. At that time the rats were sacrificed, their hearts and livers were excised, and blood samples were taken. Heart and liver weights were recorded; organ tissue and serum samples were analyzed for Zn, Cu and Fe. Hemoglobin and hemat-ocrit values were also obtained. The iron-deficient rats grew much more slowly than controls on the iron-adequate or commercial diets. The iron-deficient rats were sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Iron deficiency has been implicated in the pathogenesis of heart failure, even in the absence of frank anemia, but previous animal models of cardiomyopathy have involved systemic iron deficiency (Medeiros and Beard, 1998; Petering et al, 1990), which also causes anemia, confounding the interpretation of the role of iron in the heart. In the course of elucidating how cardiomyocytes assimilate iron, we developed a mouse mutant that allowed us to examine the consequences of isolated cardiac iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron deficiency has been implicated in the pathogenesis of heart failure, even in the absence of frank anemia, but previous animal models of cardiomyopathy have involved systemic iron deficiency (Medeiros and Beard, 1998; Petering et al, 1990), which also causes anemia, confounding the interpretation of the role of iron in the heart. In the course of elucidating how cardiomyocytes assimilate iron, we developed a mouse mutant that allowed us to examine the consequences of isolated cardiac iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 50% of patients with heart failure are iron deficient, and iron deficiency is associated with poor outcomes (Erbel et al, 2003). Severe iron deficiency causes cardiomyopathy in animals (Medeiros and Beard, 1998; Petering et al, 1990) but previous studies have neither dissociated cardiac iron deficiency from systemic iron deficiency with anemia nor investigated its cellular consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as far as we are concerned, there are no HRV studies in the literature related to patients with TT. There is increased evidence as to anemia leading to cardiac diseases and death in adults (24,25). Decreased HRV in cardiac patients was independently shown to be associated with sudden cardiac death and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Initial single-center trials focused on patients with HFrEF and iron deficiency anemia, and consistently observed improvements in peak VO 2 , patient global assessment (PGA) scores, and NT-BNP levels. 19,20 Correction of iron deficiency has also been shown to have direct effects on myocardial contractility. 7 Two meta-analyses 44, 45 reported significant improvement in echocardiography-derived LVEF with iron therapy (mean improvement +5%).…”
Section: Iron Homeostasis In Heart Failurementioning
confidence: 99%